STUDI PENGARUH UKURAN GRAIN TERHADAP KOERSIVITAS ALLOYMAGNETIK FESI (SI = 3,2 AT%) - Zulkarnain -; D. Triyono (Universitas Pasir Pengaraian, 2014)
Has researched on the influence of grain size of the alloy magnetic coercivity FeSi (Si = 3.2 at%). FeSi alloy (Si = 3.2 at%) was prepared by means of arc melting furnace. To vary the size of the grains, the alloy is annealed in a vacuum at temperatures 800oC for 30, 60 and 90 minutes. The images obtained by micro-grain size on average between 0.337 ± 0.045 mm to 0.427 ± 0.045 mm. XRD results showed that the alloy has been annealed have a higher peak intensity, FWHM width is smaller than the non-annealed alloy. Hysteresis loop of the VSM (vibrating sample magnetometer) was obtained between the coercivity (1.04 ± 0.01) x 103 up to (1.07 ± 0.01) x 103 A / m. The greater the correlation obtained grain size, the smaller coercivity with the coercivity function gain grain size is Hc (A / m) = 0.98 x 103 + 0.03 / D.